Evolution of a Pandemic and Changing Concepts in the Case Definition - Raveendran, Arkiath Veettil; Joshi, Shashank R (Journal of the Association of Physicians of India, 2024)
Pandemics result in a huge burden of cases, which paralyze the healthcare system. Proper planning and awareness of case definition at different stages of the pandemic are important for the effective utilization of resources. In this short article, we are describing the stages of a pandemic, how it ends, and the case definition at each stage of the pandemic with special reference to the recent COVID-19 pandemic.